Development of alternative rear flickering light system - Mastura Ibrahim; Siti Aishah Wahid; Sullyfaizura Mohd Rawi (Indonesian Institute For Counseling, Education and Therapy, 2020)
The lighting system of a car consist of lighting and signaling devices mounted to the front, rear and sides. The car has equipped with blinking turn signals to letting information for the other drivers. Sometimes the drivers didn’t noticed that the rear flickering light is not blinking. This condition is a major cause of accidents. The study aim to develop the Alternative Rear Flickering Light System. It is designed to turn the brake lights in flashing mode to replace the broken rear flickering signal. At the same time, a blue light indicator is placed on the dashboard to alert the driver. The system uses the Arduino programming to create hardware or programs for vehicles’ flickering light. The programming of Arduino has been tested for brake lamp (red color), blinking testing (right and left signal) and alternative flickering (brake lamp blinking). The result has been successful for several attempts the coding on Arduino. This system solves of the main problems encountered for every driver when the rear flickering light is not working. This can also turn the other drivers to be aware of the warning given on the headlights.